PERSEPSI NASABAH ATAS PROMOSI DAN PELAYANAN BMT-UGT NUSANTARA PANJI (PERSPEKTIF EKONOMI SYARIAH) - Mursidin, Syamsul; Sufyanto, Budi; Makki, Mustaqim (IAIN BONE, 2025)
This study aims to analyze the effect of promotional strategies and service quality on customer satisfaction at BMT-UGT Nusantara Panji Branch, Situbondo in the perspective of Islamic economics. BMT as an Islamic microfinance institution has a strategic role in community economic empowerment, especially in areas that have not been reached by conventional banking services. Promotion strategy and service quality are important factors in creating customer satisfaction. This research uses a descriptive qualitative approach with data collection methods through documentation studies and non-participatory observation. The results showed that promotional strategies that include advertising, sales promotion, personal selling, and publicity have a significant role in attracting customer interest. Meanwhile, service quality measured through the five dimensions of SERVQUAL, namely tangibles, reliability, responsiveness, assurance, and empathy, contributes directly to customer satisfaction. Other factors such as product quality, adequate facilities, and social responsibility also influence the level of satisfaction. The conclusion of this study confirms that effective promotion and quality service are key in increasing BMT customer satisfaction and loyalty